The Influence of Product Quality and Price to Resubscribe Intention through Customer Satisfaction as a Mediating Variable on SVoD Amazon Prime Video - Azrah Maysa Putri; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to explore the influence of product quality and price on resubscribe intention with customer satisfaction as a mediating variable in SVoD service, namely Amazon Prime Video. This study applied a quantitative approach with a data collection method in the form of a survey with a questionnaire as the research instrument. The population in this study are people who live in Jabodetabek and have used or are currently using the Amazon Prime Video streaming service. The analysis technique used in this study is the SEM-PLS (Partial Least Squares) method with a calculating tool, namely SmartPLS version 4, to assess validity, reliability, and test research hypotheses. The results of this research show that: 1) product quality influences customer satisfaction, 2) price influences customer satisfaction, 3) product quality influences resubscribe intention, 4) price influences resubscribe intention, 5) customer satisfaction influences resubscribe intention, 6) product quality influences resubscribe intention, mediated by customer satisfaction, and 7) price influences resubscribe intention, mediated by customer satisfaction. This study is expected to contribute to developing knowledge about customer behavior, especially for researchers who are interested in analyzing the relationship and influence of product quality and price on resubscribe intention through customer satisfaction.Keyword: quality product, price, resubscribe intention, customer satisfaction, subscription video on demand.